Review of the ant genus Rogeria (Hymenoptera: Formicidae) in Guyana - Lapolla, John S.; Sosa-Calvo, Jeffrey (Zootaxa, 2006)
The myrmicine ant genus Rogeria in Guyana is reviewed. Using previously published records, older collections, and collections from recent leaf litter ant survey work, nine Rogeria species are now known from Guyana, with another two species that probably also occur in Guyana. Among these eleven species, a new species, R. tsumani, is here described, and four of them, including the new species, are new records for Guyana. A key to the species found in Guyana is provided, along with illustrations of all 11 species.